Bibliometric Analysis Of Aggregated Polymers From Natural Extracts And Nanoparticles With Antimicrobial And Antifungal Activity - Gallozzo-Cárdenas, Moises (2025)
Research into polymers has been highlighted in recent years, due to the low cost, regulations on the use of plastics in different countries and the different applications that can be given to them, such as in medicine, as medical patches, and agro-industries, as containers for fruit storage. These materials have proven to be eco-friendly, since they are obtained mostly from organic materials that facilitate their rapid degradation and less contamination to our ecosystem. Due to the problems presented, research work on eco-friendly polymers is increasing since they are presented as a great candidate to solve them. In this research, articles, keywords, authors and countries with high-impact publications have been analyzed to show the current situation of polymer research. Using Excel and VOSViewer, the data obtained from Scopus from 2018 to March 2024 were analyzed. The purpose of carrying out this study was to perform an analysis of the development and trends of work on polymers with antimicrobial and antifungal activity, with adhesions of extracts or nanoparticles for applications in medicine, agroindustry, etc. The data showed a large number of articles in high-impact journals in the Scopus database, highlighting the group work being carried out, and also the countries in which more research is being carried out, highlighting India and China.